(untitled) (Costos y Gestión, 2024)
The gastronomy business at events is affected, like many others, by variables linked to the performance and physical quality of the inputs, productivity in the processes, the minimization of waste and the neutralization of the effects produced by changes in prices. of inputs and products. The GEGAVENT model aims to control the behavior of the described vectors, placing special focus on the need to optimize the economic equation of the business, achieving a service in line with the quality marketed and with consistent behavior over time. It is important to assume that this is a model designed to enhance anticipation in management. The instability in the relative prices of inputs and products adds an essential control factor for the viability of the business model. Its continuity depends on the ability to anticipate price volatility and the minimization of the effects during the time that elapses between contracting and providing the service. The objective of this paper is to present the GEGAVENT Model and its application in inflationary contexts, with interruptions in the supply of inputs and changes in their quality due to instability in relative prices throughout the chain.